The effect of variations of V-seam root face on Shielded Metal Arc Welding (SMAW) on the mechanical properties of AISI 1045 medium carbon steel - Sukmana, Irza (INSTEP Network, 2023)
Steel is an alloy primarily composed of iron (Fe) with carbon (C) as its main alloying element. Medium carbon steel, a commonly used material in the automotive industry, is known for its strength and durability. The Shielded Metal Arc Welding (SMAW) process is widely employed to join metal parts by heating and pressing them together, using a coated electrode to protect the welding arc from oxidation. One key parameter in SMAW is the root face size, as it influences the amount of filler metal in the groove area, ultimately affecting the mechanical properties of the weld. This study investigates the impact of varying root face sizes on the mechanical properties of AISI 1045 medium carbon steel. Results from the impact test show a value of 0.772 Joules, indicating a notable correlation between root face size and mechanical performance. The tensile test results reveal that larger root face sizes reduce the filler metal qu Zulmiftahantity, resulting in higher tensile strength, as AISI 1045 steel exhibits greater tensile strength than the E7016 electrode. The highest average tensile strength, recorded at a 3 mm root face, was 559.05 MPa. Visual inspections revealed several welding defects, including spatter, porosity, start-stop marks, and pinholes.